2008
DOI: 10.1007/s10661-008-0214-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and pollution sources of polycyclic aromatic hydrocarbons (PAHs) in reclaimed tidelands and tidelands of the western sea coast of South Korea

Abstract: The wide-scale reclamation of tidal flats distributed throughout the western and southern coastal areas in Korea has been completed, in an effort to expand the available arable land. The present studies were conducted in order to characterize the concentrations and compositional patterns of selected PAHs, in order to obtain more information regarding environmental risk assessments for sustainable and environment-friendly agriculture in reclaimed tidelands and tidelands in South Korea. The PAH contents were low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…High blood pressure, cerebrovascular, thyroid disease, COPD and pneumonia were found to be statistically correlated in the high exposure area. 3 Cerebrovascular, 4 Angina, 5 Myocardial infarction, 6 Diabetes, 7 Anemia, 8 Thyroid disease, 9 COPD, chronic obstructive pulmonary disease, 10 Bronchitis, 11 Pulmonary emphysema, 12 Bronchiectasis, 13 Asthma, 14 Sinus infection, 15 Allergic coryza, 16 Allergy desmatitis, 17 Bronchial asthma, 18 Acute bronchitis, 19 Pneumonia, 20 Acute pneumonia, 21 Skin Disease…”
Section: Correlation Between Air Pollution and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…High blood pressure, cerebrovascular, thyroid disease, COPD and pneumonia were found to be statistically correlated in the high exposure area. 3 Cerebrovascular, 4 Angina, 5 Myocardial infarction, 6 Diabetes, 7 Anemia, 8 Thyroid disease, 9 COPD, chronic obstructive pulmonary disease, 10 Bronchitis, 11 Pulmonary emphysema, 12 Bronchiectasis, 13 Asthma, 14 Sinus infection, 15 Allergic coryza, 16 Allergy desmatitis, 17 Bronchial asthma, 18 Acute bronchitis, 19 Pneumonia, 20 Acute pneumonia, 21 Skin Disease…”
Section: Correlation Between Air Pollution and Diseasementioning
confidence: 99%
“…Previous studies of the past have shown that air pollution directly affects lung disease and respiratory diseases in the United States in 1948, a case of air pollution in Pennsylvania, USA [5][6][7]. In Korea, it has been confirmed that the application of industrial deterrence (Yeosu, Gwangyang, Ulsan, Pohang, Ansan) has increased as a factor of cancer occurrence and disease in recent years through the process of establishing industrial complexes in major economic development since 1970 [8,9] Among them, heavy metals and chemicals in Korea are identified as air pollutants, and fine dust due to fuel consumption is also confirmed [10,11]. As a result, the emission factors of odor, air pollution, soil pollution, and heavy metals directly affect the residents of the area due to the composition of the industrial complex.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the past have shown that air pollution directly affects lung disease and respiratory diseases in the United States in 1948, a case of air pollution in Pennsylvania, USA [5,6,7]. In Korea, it has been confirmed that the application of industrial deterrence (Yeosu, Gwangyang, Ulsan, Pohang, Ansan) has increased as a factor of cancer occurrence and disease in recent years through the process of establishing industrial complexes in major economic development since 1970 [8,9] Among them, heavy metals and chemicals in Korea are identified as air pollutants, and fine dust due to fuel consumption is also confirmed [10,11]. As a result, the emission factors of odor, air pollution, soil pollution, and heavy metals directly affect the residents of the area due to the composition of the industrial complex.…”
Section: Introductionmentioning
confidence: 96%
“…One is anthropogenic sources, such as the incomplete combustion of fossil fuels, e-waste and sewage sludge (Peng et al, 2011). The other is natural sources, like forest fires and volcanic eruptions (Cho et al, 2009). Their influences on human health and ecosystems are of great concern to researchers.…”
Section: Introductionmentioning
confidence: 99%